Strategy of Public Image Recovery on Instagram; Case Study of Athlete Cristiano Ronaldo's Negative News Scandal - Dewi Gusriani; Ucik Ana Fardila (UIN Salatiga, 2021)
Public image is a person's view of self-image in order to appear to give a good and positive impression in the eyes of the public. Instagram is referred to as one of the social media to build, maintain and restore image by posting uploads that contain positive ideas and provide good comments. Image recovery is carried out when someone experiences an image crisis due to negative news and news so that the positive image decreases. Image decline can happen to anyone, including the world's number one soccer athlete who managed to score 600 goals on April 28, 2019 and won the Golden Soes award 4 times in 2007, 2010, 2013 and 2014. Many achievements have been achieved by a football athlete from Portugal. This makes the popularity more attached and ogled by big companies to become brand ambassadors and become a public figure. The high popularity made the image of Cristiano Ronaldo highlighted by many audiences, but at the end of 2020 news about the rape scandal, the violation of COVID-19 protocols emerged until his new case in January 2021, namely sexual harassment. The existence of negative news made Cristiano Ronaldo not remain silent so that he immediately restored his image through positive uploads on his personal Instagram media account, which became interesting to study. The method used in this research is descriptive qualitative with the approaches used is semiotics and and image recovery theory. The results in this study are to find out the strategies used by Cristiano Ronaldo in fighting the image crisis through Instagram @cristiano and the model for uploading content on his Instagram to provide a positive image perception to the public. Cristiano Ronaldo can provide an example and inspiration for the public, especially other artists and athletes in order to maintain a positive image.